THE EFFECT OF CORPORATE GOVERNANCE ON CAPITAL STRUCTURE IN COMPANIES LISTED ON THE IDX - Putra, Joni Eka; Patrisia, Dina (JURNAL ECONOMICA : Research of Economic And Economic Education, 2023)
This study aims to analyze the influence of corporate governance on the capital structure of companies listed on the IDX. Data collection is done by the method of documentation with secondary data. The population of this study are real estate and property companies listed on the IDX, as many as 59 real estate and property companies listed on the IDX from 2017-2021. Determination of the sample using purposive sampling with a final sample of 119 observations after outliers . Analysis of the research data used multiple linear regression analysis using the SPSS Version 23 program. The results showed that foreign ownership, institutional ownership and independent commissioners had a significant effect, while managerial ownership, shareholders and the number of commissioners had no significant effect on capital structure.